Dynamics of land use and agricultural growth: A study in Kerala - Elumalai Kannan; Sheeba Andrews (Bengaluru, 2017)
Traditionally, land has been considered an important resource for agricultural production with people earning their livelihood by way of cultivating land. However, the concept of land has undergone changes overtime, with a change the in structure of socie
Keywords: Economics